Honeycomb structure and honeycomb filter

JP2026166788APending Publication Date: 2026-10-14NGK CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025059967
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14
Estimated Expiration
2045-03-31

AI Technical Summary

Benefits of technology

【0021】 本発明によれば、外周コート層への触媒の付着を抑制しながら、ハニカム基材上に触媒を付着させることが可能なハニカム構造体及びハニカムフィルタが提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166788000001_ABST
    Figure 2026166788000001_ABST
Patent Text Reader

Abstract

The present invention provides a honeycomb structure and a honeycomb filter that enable selective deposition of a catalyst onto a honeycomb substrate while suppressing the deposition of the catalyst onto the outer coating layer. [Solution] The honeycomb substrate 10 has porous partition walls 12 that divide and form a plurality of cells 11 that form a fluid flow path extending from an inlet end face 14 to an outlet end face 15, and a porous outer coating layer 13 disposed on the outer surface of the honeycomb substrate 10, wherein the honeycomb substrate 10 has pores in the partition walls 12 having a pore diameter that causes capillary action, and when the average pore diameter of the honeycomb substrate 10 is B [μm] and the average pore diameter of the outer coating layer 13 is A [μm], B
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a honeycomb structure and a honeycomb filter. [Background technology]

[0002] Honeycomb structures and honeycomb filters using them are known as devices for collecting particulate matter or purifying toxic gas components emitted from internal combustion engines of automobiles and other vehicles. Honeycomb structures are manufactured by extruding a ceramic clay mixture, obtained by mixing raw material powder, molding aids, pore-forming agent raw materials, and water, using a special mold, drying it in a drying oven, and firing it in a firing furnace. In recent years, with the increase in diameter and thinning of cells of honeycomb structures, it has become difficult to obtain the dimensional accuracy and mechanical strength required for the product. As one method to improve dimensional accuracy and mechanical strength, it is common practice to grind the outer circumference of the molded body and then apply an outer circumference coating material to the surface to create an outer circumference wall.

[0003] Japanese Patent Publication No. 2004-75523 (Patent Document 1) describes a ceramic honeycomb structure having a large number of flow holes separated by cell walls, in which the peripheral edge of the structure is removed by processing, and then an outer peripheral coating material is applied to the outer peripheral surface to form an outer peripheral wall.

[0004] In recent years, there has been a growing demand for lighter honeycomb structures and honeycomb filters to improve fuel efficiency in automobiles, and increasing the porosity of the outer coating material is one proposed solution. However, increasing the porosity of the outer coating material presents a problem: a large amount of catalyst adheres to the outer coating material during catalyst application. Furthermore, increasing the porosity of the outer coating material can also lead to the catalyst leaking out of the honeycomb structure during application.

[0005] As one way to solve such problems, for example, Japanese Patent Publication No. 2009-183835 (Patent Document 2) proposes a method in which the outer surface of a honeycomb segment joint is machined, a catalyst is supported on the surface of the resulting machined body to create a catalyst support body, and an outer surface coating layer is placed on the outer surface of the catalyst support body.

[0006] Furthermore, Japanese Patent Publication No. 5431158 (Patent Document 3) describes a method for producing a catalyst support in which a magnetoplanvite-type composite oxide is generated by filling the pores with an aqueous solution using a pore-filling method that utilizes capillary action occurring in the pores of porous alumina, drying, and then calcining. [Prior art documents] [Patent Documents]

[0007] [Patent Document 1] Japanese Patent Publication No. 2004-75523 [Patent Document 2] Japanese Patent Publication No. 2009-183835 [Patent Document 3] Patent No. 5431158 [Overview of the project] [Problems that the invention aims to solve]

[0008] Catalysts are sometimes supported on honeycomb structures by dip coating, which involves immersing the honeycomb structure in a catalyst solution. However, during this coating process, the catalyst also adheres to the outer coating layer. Since the catalyst solution used for supporting the catalyst contains precious metals such as platinum (Pt), it is desirable to minimize the adhesion of the catalyst to the outer coating layer in order to reduce the amount of catalyst used.

[0009] However, the invention described in Patent Document 1 only proposes a method for making the thermal expansion coefficient of the outer periphery wall smaller than the radial thermal expansion coefficient of the cell wall, and does not describe how to support a catalyst on a ceramic honeycomb structure. The invention described in Patent Document 2 is desirable in that it can suppress the adhesion of the catalyst to the outer periphery coating layer, but there is room to consider other methods besides those described in Patent Document 2. The invention described in Patent Document 3 also does not describe any knowledge regarding catalyst adhesion to a honeycomb structure equipped with an outer periphery coating layer.

[0010] In view of the above problems, the present invention provides a honeycomb structure and a honeycomb filter capable of selectively depositing a catalyst on a honeycomb substrate while suppressing the deposition of the catalyst on the outer peripheral coat layer. Means for Solving the Problems

[0011] As a result of intensive studies to solve the above problems, the present inventors focused on the balance between the pore diameter of the honeycomb substrate and the pore diameter of the outer peripheral coat layer disposed on the outer peripheral surface of the honeycomb substrate, and have completed the present invention. That is, the present invention is exemplified as follows.

[0012] [Aspect 1] In one embodiment, the present invention is a columnar honeycomb structure including a porous partition wall that partitions and forms a plurality of cells serving as fluid flow paths extending from an inflow end face to an outflow end face, and a porous outer peripheral coat layer disposed on the outer peripheral surface of the honeycomb substrate, wherein the honeycomb substrate has pores with pore diameters that cause capillary action in the partition wall, and when the average pore diameter of the honeycomb substrate is defined as B [μm] and the average pore diameter of the outer peripheral coat layer is defined as A [μm], the relationship of B<A is satisfied.

[0013] [Aspect 2] In another embodiment, the present invention is the honeycomb structure according to Aspect 1, wherein when the average porosity of the honeycomb substrate is defined as P2 [%] and the average porosity of the outer peripheral coat layer is defined as P1 [%], A>B×(P1 / P2) 0.2 is satisfied.

[0014] [Aspect 3] In still another embodiment, the present invention is the honeycomb structure according to Aspect 1 or 2, wherein when the average porosity of the outer peripheral coat layer is defined as P1 [%], A<670-1 / 6×P1 2 is satisfied.

[0015] [Aspect 4] In still another embodiment, the present invention is the honeycomb structure according to any one of Aspects 1 to 3, wherein the average pore diameter B of the honeycomb substrate is 5 μm to 30 μm.

[0016] [Aspect 5] In still another embodiment, the present invention is the honeycomb structure according to any one of Aspects 1 to 4, wherein the average pore diameter A of the outer peripheral coat layer is more than 5 μm and 500 μm or less.

[0017] [Aspect 6] In still another embodiment, the present invention is the honeycomb structure according to any one of Aspects 1 to 5, wherein the average porosity P2 of the honeycomb substrate is 20 to 70%.

[0018] [Aspect 7] In still another embodiment, the present invention is the honeycomb structure according to any one of Aspects 1 to 6, wherein the average porosity P1 of the outer peripheral coat layer is 30 to 75%.

[0019] [Aspect 8] In still another embodiment, the present invention is the honeycomb structure according to any one of Aspects 1 to 7, wherein the honeycomb substrate includes a plurality of honeycomb substrates, the plurality of honeycomb substrates are joined by a joining layer that joins the plurality of honeycomb substrates to each other, and the outer peripheral coat layer is disposed so as to surround the outer peripheral surfaces of the plurality of honeycomb substrates joined by the joining layer.

[0020] [Aspect 9] In still another embodiment, the present invention is a honeycomb filter including a columnar honeycomb substrate having porous partition walls that define a plurality of cells serving as fluid flow paths extending from an inflow end face to an outflow end face, and a porous outer peripheral coat layer disposed on the outer peripheral surface of the honeycomb substrate, wherein the honeycomb substrate has pores with pore diameters that cause a capillary phenomenon in the partition walls, a catalyst is supported on the partition walls, and when the average pore diameter of the honeycomb substrate is defined as B [μm] and the average pore diameter of the outer peripheral coat layer is defined as A [μm], the relationship of B < A is satisfied. [Effects of the Invention]

[0021] According to the present invention, it is possible to provide a honeycomb structure and a honeycomb filter capable of depositing a catalyst on the honeycomb substrate while suppressing the adhesion of the catalyst to the outer peripheral coat layer. [Brief explanation of the drawing]

[0022] [Figure 1] This is a perspective view of a honeycomb structure according to an embodiment of the present invention. [Modes for carrying out the invention]

[0023] Embodiments of the present invention will be described below with reference to the drawings. Note that the embodiments shown below are illustrative examples of devices and methods for realizing the technical concept of this invention, and the technical concept of this invention is not limited to the structure, arrangement, etc., of the components described below.

[0024] <Honeycomb structure> As shown in Figure 1, the honeycomb structure 1 according to an embodiment of the present invention comprises a columnar honeycomb base material 10 having porous partition walls 12 that divide and form a plurality of cells 11 that serve as fluid flow paths extending from an inlet end face 14 to an outlet end face 15, and a porous outer periphery coating layer 13 disposed on the outer periphery surface of the honeycomb base material 10.

[0025] The external shape of the honeycomb structure 1 is not particularly limited, and the cross section perpendicular to the direction in which the cells 11 extend can be cylindrical, oval, polygonal (quadrilateral, pentagonal, hexagonal, heptagonal, octagonal, etc.), or columnar. Figure 1 shows an example of a honeycomb structure 1 in which the external shape is circular in the cross section perpendicular to the direction in which the cells 11 extend.

[0026] The diameter of the end face of the honeycomb structure 1 is not particularly limited and can be set appropriately according to the application and required performance. If the diameter of the end face of the honeycomb structure 1 is too large, the difficulty of manufacturing increases, so the diameter of the end face is preferably 30 to 600 mm, and more preferably 50 to 500 mm. Note that the diameter of the end face of the honeycomb structure 1 refers to the diameter if the outer shape is circular, and to the equivalent diameter if the outer shape is not circular. If the end face of the honeycomb structure 1 is square, the length of one side of the inlet end face 14 and the outlet end face 15 is preferably 35 to 500 mm, and more preferably 100 to 200 mm.

[0027] The material of the honeycomb substrate 10 is not particularly limited, and porous ceramics can be used. Examples of ceramics include cordierite, mullite, zirconium phosphate, aluminum titanate, silicon carbide, silicon-silicon carbide composites (e.g., Si-bonded SiC), cordierite-silicon carbide composites, zirconia, spinel, indialite, sapphirin, corundum, titania, and silicon nitride. These ceramics may be contained individually or in combination of two or more. Other materials for the honeycomb substrate 10 include porous sintered metals containing alloy components mainly composed of one or more elements selected from the group consisting of Fe, Cr, Mo, and Ni.

[0028] In one embodiment, the honeycomb substrate 10 is preferably formed from a material mainly composed of cordierite. When the honeycomb substrate 10 is mainly composed of cordierite, it is preferable that the honeycomb substrate 10 contains 50% by mass or more, preferably 60% by mass or more, of cordierite.

[0029] In one embodiment, the honeycomb substrate 10 is preferably formed from a material mainly composed of silicon carbide material or carbon-silicon carbide composite material. Among porous ceramics, silicon-silicon carbide composite material is suitable for filter applications because it has excellent properties in heat resistance, thermal shock resistance, and oxidation resistance. The silicon-silicon carbide composite material contains silicon carbide particles as aggregate and silicon as a binder to bind the silicon carbide particles together. In this silicon-silicon carbide composite material, it is preferable that multiple silicon carbide particles are bound together by silicon such that pores are formed between the silicon carbide particles.

[0030] Furthermore, when silicon carbide material or carbon-silicon carbide composite material is the main component, it is preferable that the silicon carbide material or carbon-silicon carbide composite material be present in an amount of 50% by mass or more of the total, more preferably 60% by mass or more, and even more preferably 70% by mass or more. The blending ratio of silicon and silicon carbide in the honeycomb base material 10, the type of firing aid and its blending ratio can be appropriately adjusted according to the required dimensions and application.

[0031] The shape of the cell 11 is not particularly limited, but in a cross section perpendicular to the direction in which the cell 11 extends, it may have any shape such as a triangle, square, pentagon, hexagon, octagon, or other polygon, a circle, or an ellipse, or it may be irregular in shape. By providing cells 11 of such shape, the pressure loss when air flows can be reduced. Figure 1 shows an example of a honeycomb structure 1 in which the shape of the cell 11 is square in a cross section perpendicular to the direction in which the cell 11 extends.

[0032] The density of cells 11 (number of cells 11 per unit cross-sectional area) is not particularly limited, but is typically between 15 and 77 cells / cm³. 2 It is preferable to set the range to 20-62 cells / cm². 2 It is more preferable to set the range to 23-54 cells / cm². 2It is even more preferable to set the range within this range. The density of cells 11 is the value obtained by dividing the number of cells 11 in the honeycomb structure 1 in a cross section perpendicular to the direction in which the cells 11 extend by the area of ​​the honeycomb structure 1 excluding the outer coating layer 13, and can be measured by microscopic observation using a microscope or the like.

[0033] The thickness of the partition walls 12 that divide the cells 11 is not particularly limited, but from the viewpoint of weight reduction and pressure loss reduction, it is preferable to make them as thin as possible. On the other hand, if the thickness of the partition walls 12 is made too thin, the mechanical strength may be insufficient. For example, the thickness of the partition walls 12 is preferably 75 to 500 μm, more preferably 100 to 450 μm, and even more preferably 125 to 400 μm. The thickness of the partition walls 12 is the length that a line segment connecting the centroids of adjacent cells 11 crosses the partition walls 12 in a cross section perpendicular to the direction in which the cells 11 extend, and can be measured by microscopic observation using a microscope or the like.

[0034] The outer periphery coating layer 13 is formed on the outer surface of the honeycomb substrate 10 to a predetermined thickness. This outer periphery coating layer 13 can be formed by applying a slurry-like outer periphery coating material, which contains ceramic material, to the outer surface of the honeycomb substrate 10. The outer periphery coating layer 13 is formed after processing the outer surface of the honeycomb substrate 10. This allows deformed cells 11 that may form on the outer surface during the manufacturing of the honeycomb substrate 10 to be removed in advance before the formation of the outer periphery coating layer 13, thereby improving the mechanical strength of the honeycomb structure 1. Furthermore, dimensional accuracy is also improved by forming the outer periphery coating layer 13 on the outer surface of the honeycomb substrate 10 after processing it to the desired dimensions.

[0035] The material of the outer coating layer 13 is not particularly limited, but is usually made of a ceramic material. For example, cordierite, silicon carbide, or titanium oxide can be used as materials for the outer coating layer 13. It is preferable to use the same material for the outer coating layer 13 as the main component of the material constituting the honeycomb substrate 10, as this reduces the difference in thermal expansion coefficients between the honeycomb substrate 10 and the outer coating layer 13. In addition to the ceramic material mentioned above, the outer coating layer 13 may also contain a binder, dispersion medium, additives, etc.

[0036] The thickness of the outer periphery coating layer 13 is not particularly limited, but a thickness of 0.1 to 3.0 mm can improve thermal shock resistance and other properties. The thickness of the outer periphery coating layer 13 is preferably 0.15 to 2.5 mm, and more preferably 0.2 to 2 mm. The thickness of the outer periphery coating layer 13 refers to the length in the normal direction from the boundary between the outermost cell 11 partition wall 12 and the outer periphery coating layer 13 to the outer surface of the honeycomb structure 1 in a cross section perpendicular to the direction in which the cell 11 extends. The thickness of the outer periphery coating layer 13 is the average value obtained by measuring each of the eight measurement points at 45° intervals in the circumferential direction of the end face of the honeycomb structure 1 using a microscope.

[0037] Capillary action is the phenomenon in which the liquid inside a capillary moves within the capillary without external energy input, and is mainly caused by surface tension. The height (h) of the rise in the liquid level due to capillary action can generally be expressed by the following equation (1). h=2Tcosθ / (ρ·g·r) ···(1) Here, T is the surface tension of the liquid, θ is the contact angle (angle of the contact surface between the liquid and the solid), ρ is the density of the liquid, g is the acceleration due to gravity, and r is the inner diameter (radius) of the capillary.

[0038] In the present embodiment, this capillary phenomenon is utilized to carry out catalyst supporting on the honeycomb structure 1. That is, the honeycomb substrate 10 according to the present embodiment is provided with pores having a pore diameter that causes a capillary phenomenon in the partition walls 12, and when the average pore diameter of the honeycomb substrate 10 is defined as B [μm] and the average pore diameter of the outer peripheral coat layer 13 is defined as A [μm], the relationship of B < A is satisfied.

[0039] According to the honeycomb structure 1 according to the present embodiment, at the time of catalyst supporting, the catalyst liquid containing the catalyst leaches from the pores on the surfaces of the partition walls 12 of the honeycomb substrate 10 into the inside of the partition walls 12 by the capillary phenomenon. The average pore diameter A of the outer peripheral coat layer 13 is larger than the average pore diameter B of the honeycomb substrate 10. Therefore, as can be understood from the formula (1), the depth at which the catalyst liquid leaches from the surface to the inside due to the capillary phenomenon is greater in the honeycomb substrate 10 than in the outer peripheral coat layer 13. According to the honeycomb structure 1 of the present embodiment, more catalyst can be deposited on the honeycomb substrate 10 than on the outer peripheral coat layer 13 of the honeycomb structure 1.

[0040] The pores formed in the partition walls 12 that cause the capillary phenomenon are preferably formed in the entire honeycomb substrate 10 from the viewpoint of production ease, but the pores may be selectively formed only in the surface layer portions of the partition walls 12. When the pores are selectively formed only in the surface layer portions of the partition walls 12, the average pore diameter B of the honeycomb substrate 10 according to the present embodiment means the average pore diameter of the pores in the portions where the pores are formed. When the pores are formed in the entire honeycomb substrate 10, the average pore diameter B of the honeycomb substrate 10 means the pore diameter of the entire honeycomb substrate 10.

[0041] In the catalyst loading onto the honeycomb structure 1 utilizing capillary action, not only the pore diameters of the honeycomb substrate 10 and the outer peripheral coat layer 13, but also their porosities can be involved. Therefore, in the present embodiment, it is preferable to consider the pore characteristics including the average porosity in addition to the average pore diameter A of the honeycomb substrate 10 and the outer peripheral coat layer 13. That is, when the average pore diameter of the honeycomb substrate 10 according to the present embodiment is B [μm], the average pore diameter of the outer peripheral coat layer 13 is A [μm], the average porosity of the honeycomb substrate 10 is P2 [%], and the average porosity of the outer peripheral coat layer 13 is P1 [%], it is preferable to satisfy the relationship of the following formula (2) in addition to the relationship of B<A. A>B×(P1 / P2) 0.2 ···(2) When the average pore diameters A, B and the average porosities P1, P2 of the honeycomb substrate 10 and the outer peripheral coat layer 13 satisfy the relationship of the formula (2), it becomes possible to selectively deposit the catalyst on the honeycomb substrate 10 while suppressing the adhesion of the catalyst to the outer peripheral coat layer 13, and to suppress the exudation of the catalyst from the outer peripheral coat layer 13 during catalyst loading.

[0042] For the catalyst loading onto the honeycomb structure 1 utilizing capillary action, it is preferable to take empirical phenomena into account, including viewpoints from manufacturing, such as that the pores formed in the partition walls 12 of the honeycomb substrate 10 do not actually have the tubular shape assumed in the formula (1), that the viscosity of the catalyst solution to be leached into the pores of the partition walls 12 can affect the leaching depth of the catalyst solution by capillary action, or that catalyst leakage actually occurs when the catalyst is loaded onto the honeycomb structure 1 using capillary action. As a result of comprehensively considering these empirical phenomena, in the honeycomb structure 1 according to the embodiment of the present invention, when the average pore diameter of the outer peripheral coat layer 13 is A [μm], the average pore diameter of the honeycomb substrate 10 is B [μm], and the average porosity of the outer peripheral coat layer 13 is P1 [%], it is more preferable to satisfy the relationship of the following relational expression (3) in addition to the relationship of B<A. A<670-1 / 6×P1 2 ···(3) When the average pore diameter A and the average porosity P1 of the outer peripheral coat layer 13 satisfy the relationship of formula (3), it is possible to suppress leakage of the catalyst from the honeycomb structure 1 during catalyst coating, suppress adhesion of the catalyst to the outer peripheral coat layer 13, suppress exudation, allow a larger amount of the catalyst to adhere into the pores of the partition walls 12 of the honeycomb base material 10, and support a predetermined amount of the catalyst on the honeycomb structure 1. It is more preferable that the honeycomb structure 1 according to the embodiment of the present invention satisfies the relationship of formula (2) and / or formula (3) in addition to the relationship of B<A.

[0043] The average pore diameters A, B and the average porosities P1, P2 can be derived as follows using images (SEM images) obtained by observation with a scanning electron microscope (SEM). First, the honeycomb structure 1 including the honeycomb base material 10 and the outer peripheral coat layer 13 is cut such that a cross section perpendicular to the extending direction of the cells 11 serves as an observation surface, and the cut surface is subjected to resin embedding and polishing to obtain an observation sample. The magnification of the SEM is set to 100 to 500 times, and the observation surface of the observation sample is photographed to obtain SEM images of the honeycomb base material 10 and the outer peripheral coat layer 13. The SEM images can be subjected to image analysis with commercially available image analysis software. In the image analysis, for example, a threshold value is determined by a discriminant analysis method from the luminance distribution of the luminance data of the pixels in the SEM image. Based on the determined threshold value, each pixel in the SEM image is binarized into a solid portion and a pore portion, and the area of the solid portion and the area of the pore portion are calculated. The ratio of the area of the pore portion to the total area (the total area of the solid portion and the pore portion) is defined as the porosity (unit: %). The pore diameter is calculated using generally available software that calculates the pore diameter by fitting an inscribed circle inscribed in the pore in the SEM image. The available software is not particularly limited, and for example, the calculation can be performed using PoreSpy or the like available from the open source of Python. The above measurement is repeated 5 times to derive the average pore diameters A, B and the average porosities P1, P2.

[0044] If the average pore diameter A and average porosity P1 of the outer coating layer 13 are made too large, the catalyst retention capacity within the pores due to capillary action is lost, and the catalyst may leak out. In particular, if the average pore diameter A is made too large when the average porosity P1 of the outer coating layer 13 is increased, the amount of catalyst leakage may increase. On the other hand, if the average pore diameter A and average porosity P1 of the outer coating layer 13 are made too small, the catalyst retention capacity within the pores due to capillary action increases, and a large amount of catalyst may adhere to the outer coating layer 13.

[0045] The average pore diameter A of the outer coating layer 13 is not limited to the following, but is preferably greater than 5 μm and less than or equal to 500 μm, more preferably between 6 and 400 μm, and even more preferably between 6.5 and 300 μm. In one embodiment, the average pore diameter A may be 6.5 to 60 μm, and in another embodiment, it may be 20 to 60 μm. In yet another embodiment, the average pore diameter A may be 100 to 450 μm, and in yet another embodiment, it may be 110 to 300 μm. The average porosity P1 of the outer coating layer 13 is not particularly limited, but is preferably 30 to 75%, more preferably between 32 to 70%, and even more preferably between 34 to 60%. In one embodiment, the average porosity P1 may be 30 to 60%, and in another embodiment, it may be 30 to 35%.

[0046] The average pore diameter B of the honeycomb substrate 10 is not limited to the following, but is preferably 5 to 30 μm, more preferably 5 to 26 μm, and even more preferably 6 to 24 μm. In one embodiment, the average pore diameter B may be 9 to 18 μm, and in another embodiment, it may be 12 to 18 μm. The average porosity P2 of the honeycomb substrate 10 is not particularly limited, but is preferably 20 to 70%, more preferably 30 to 67%, and even more preferably 35 to 65%. In one embodiment, the average porosity P2 may be 30 to 65%, and in another embodiment, it may be 40 to 55%.

[0047] In order to exhibit capillary action suitable for catalyst support, the average pore diameter A of the outer coating layer 13 is preferably 2 to 420 μm larger, more preferably 5 to 300 μm larger, and even more preferably 10 to 150 μm larger than the average pore diameter B of the honeycomb substrate 10, although this is not limited to the above.

[0048] According to the honeycomb structure 1 of the present invention, the porous honeycomb substrate 10 constituting the honeycomb structure 1 has an average pore diameter A suitable for coating a catalyst using capillary action, and the average pore diameter A of the outer periphery coating layer 13 is larger than the average pore diameter B of the honeycomb substrate 10. Therefore, according to the honeycomb structure 1 of the present invention, when loading a catalyst using capillary action, it is possible to adhere more catalyst to the honeycomb substrate 10 while suppressing the adhesion of the catalyst to the outer periphery coating layer 13.

[0049] <zygote> In an embodiment of the present invention, the honeycomb structure 1 comprises a plurality of honeycomb substrates 10, which are joined together by a bonding layer, and the outer peripheral coating layer 13 is arranged to surround the outer peripheral surfaces of the plurality of honeycomb substrates 10 joined by the bonding layer, thereby forming a joined body. The number of honeycomb substrates 10 constituting the joined body is not particularly limited and can usually be about 9 to 16.

[0050] The bonding layer is formed by applying a paste-like bonding material to the outer surface of multiple honeycomb substrates 10, and then drying and curing it. The bonding material used to form the bonding layer is preferably composed of a material mainly consisting of a filler made of heat-resistant ceramic fibers, ceramic particles, etc., and an inorganic adhesive such as colloidal silica.

[0051] In the joined body, a plurality of honeycomb substrates 10 are joined to each other via the joining layer, so that thermal stress is relaxed in the joining layer. Therefore, even when a rapid temperature change of exhaust gas or local heat generation occurs, the occurrence of cracks in the honeycomb substrates 10 can be suppressed. In addition, since the joined body is formed by joining a plurality of honeycomb substrates 10 via the joining layer, cutting the outer peripheral portion thereof to a desired dimension, and then forming the outer peripheral coat layer 13, the dimensional accuracy of the joined body can also be improved.

[0052] <Filter> A honeycomb filter can be produced using the honeycomb structure 1 according to the embodiment of the present invention. The honeycomb filter includes a columnar honeycomb substrate 10 having porous partition walls 12 that define a plurality of cells 11 serving as fluid flow paths extending from an inflow end face 14 to an outflow end face 15, and a porous outer peripheral coat layer 13 disposed on the outer peripheral surface of the honeycomb substrate 10. The honeycomb substrate 10 has pores with pore diameters that cause a capillary phenomenon in the partition walls 12, a catalyst is supported on the partition walls 12, and when the average pore diameter of the honeycomb substrate 10 is B [μm] and the average pore diameter of the outer peripheral coat layer is A [μm], the relationship of B<A is satisfied.

[0053] Plugging portions may be formed in the plurality of cells 11 defined by the porous partition walls 12 so as to form a complementary checkered pattern on the inflow end face 14 and the outflow end face 15. By forming such plugging portions in the cells 11, when a fluid flows through a diesel particulate filter (DPF) using the honeycomb filter according to the present embodiment, the fluid does not directly pass from the inflow end face 14 to the outflow end face 15, but passes through the catalyst-supported partition walls 12 at least once. By causing the fluid to pass through the catalyst-supported partition walls 12, particulate matter contained in the fluid can be removed.

[0054] <Catalyst> In the honeycomb structure 1 and honeycomb filter according to embodiments of the present invention, the catalyst is supported on the partition wall 12 by catalyst support using capillary action. The catalyst is not particularly limited as long as it can burn particulate matter with the heat of the exhaust gas. As such a catalyst, for example, elements selected from noble metals, elements of Group VIa of the periodic table, and elements of Group VIII of the periodic table can be used as elements or compounds. More specifically, elements such as platinum (Pt), palladium (Pd), rhodium (Rh), nickel (Ni), cobalt (Co), molybdenum (Mo), tungsten (W), cerium (Ce), copper (Cu), vanadium (V), iron (Fe), gold (Au), and silver (Ag) can be used as catalysts. NOx selective reduction catalyst components and NOx storage catalyst components may be used as catalysts.

[0055] The amount of catalyst supported on the partition walls 12 of the honeycomb substrate 10 by catalyst loading using capillary action varies depending on the catalyst used, the average pore size and average porosity of the honeycomb substrate 10, etc., and is not limited to the following, but is preferably 10 to 200 g / L, and more preferably 50 to 150 g / L. The amount of catalyst loaded can be calculated, for example, by cutting out a block of a specific volume from the honeycomb substrate 10 in the central part in the direction in which the cells 11 of the honeycomb structure 1 extend after catalyst loading, and dividing the mass difference before and after catalyst loading by the volume cut out.

[0056] In catalyst loading using capillary action, the inlet end face 14 and outlet end face 15 of the honeycomb structure 1 are immersed in a catalyst solution containing the catalyst for a certain period of time, and the catalyst solution is permeated by capillary action from the inlet end face 14 or outlet end face 15 in the direction in which the cells 11 extend. Therefore, the concentration of the catalyst in the catalyst solution immersed in the solution is highest at the inlet end face 14 or outlet end face 15, and tends to gradually decrease from the inlet end face 14 to the outlet end face 15, or from the outlet end face 15 to the inlet end face 14. Thus, in the honeycomb filter obtained by heat-treating this honeycomb structure 1, the catalyst is loaded such that the amount loaded gradually decreases from the inlet end face 14 to the outlet end face 15, or from the outlet end face 15 to the inlet end face 14. The state of catalyst loading on the honeycomb structure 1 can be evaluated by observing a sample cut along the direction in which the cells 11 of the honeycomb structure 1 extend using a scanning electron microscope (SEM).

[0057] <Manufacturing method> A method for manufacturing a honeycomb structure 1 according to an embodiment of the present invention includes (a) a step S1 for manufacturing a honeycomb substrate 10, (b) a step S2 for machining the outer surface of the honeycomb substrate 10, (c) a step S3 for forming an outer surface coating layer 13 on the outer surface of the honeycomb substrate 10 to manufacture a honeycomb structure 1, and (d) a step S4 for supporting a catalyst on the honeycomb structure 1 using capillary action. The following example describes the case in which cordierite is used as a ceramic raw material for manufacturing the honeycomb structure 1.

[0058] In step S1, a raw material composition containing ceramic raw materials, a dispersion medium, a pore-forming material, and a binder is kneaded to produce a clay base, which is then extruded and dried to produce the honeycomb substrate 10. Additives such as dispersants can be added to the raw material composition as needed. When extruding, a die having the desired overall shape, cell shape, partition wall thickness, cell density, etc., can be used.

[0059] Examples of ceramic raw materials include cordierite, mullite, zirconium phosphate, aluminum titanate, silicon carbide, silicon-silicon carbide composites (e.g., Si-bonded SiC), cordierite-silicon carbide composites, zirconia, spinel, indialite, sapphirin, corundum, titania, and silicon nitride. Specifically, though not limited to these, examples include silicon carbide, silicon, silica, talc, alumina, kaolin, serpentine, pyroferrite, brucite, boehmite, mullite, magnesite, and aluminum hydroxide. In addition, silicon oxide, strontium oxide, and aluminum oxide added as firing aids are also types of ceramic raw materials. Ceramic raw materials may be used individually or in combination of two or more types.

[0060] Examples of dispersion media include water, or a mixed solvent of water and an organic solvent such as alcohol, but water is particularly suitable. The amount of dispersion media can be 25 to 45 parts by mass per 100 parts by mass of ceramic raw material.

[0061] The pore-forming agent is not particularly limited as long as it forms pores after firing, and examples include wheat flour, starch, foamed resin, superabsorbent resin, silica gel, carbon (e.g., graphite, coke), ceramic balloons, polyethylene, polystyrene, polypropylene, nylon, polyester, acrylic, phenol, etc. The pore-forming agent may be used alone or in combination of two or more types. From the viewpoint of forming pores in the honeycomb substrate 10 that cause capillary action and adjusting the honeycomb substrate 10 to a porosity suitable for catalyst support using capillary action, the content of the pore-forming agent is preferably 1.0 to 30.0 parts by mass, more preferably 3 to 27 parts by mass, and even more preferably 5 to 24 parts by mass per 100 parts by mass of ceramic raw material.

[0062] Examples of binders include organic binders such as methylcellulose, hydroxypropyl methylcellulose, hydroxyethylcellulose, carboxymethylcellulose, and polyvinyl alcohol. In particular, the combined use of methylcellulose and hydroxypropyl methylcellulose is preferred. The binder content is preferably 3 to 10 parts by mass, more preferably 4 to 9 parts by mass, and even more preferably 5 to 8 parts by mass, per 100 parts by mass of ceramic raw material. The binder may be used alone or in combination of two or more types. Examples of dispersants include ethylene glycol, dextrin, fatty acid soap, and polyether polyol. The dispersant content can be 0 to 3 parts by mass, more preferably 0.1 to 2.5 parts by mass, and even more preferably 0.2 to 2.0 parts by mass, per 100 parts by mass of ceramic raw material.

[0063] When sealing the inlet end face 14 and outlet end face 15 of a honeycomb molded body, the method is not particularly limited, and a well-known method such as filling the cell openings of the inlet end face and outlet end face, to which a predetermined mask has been applied, with a sealing slurry can be used. The material of the sealing portion is not particularly limited, but it is preferably a ceramic from the viewpoint of strength and heat resistance. Preferably, the ceramic is one or more of the following: cordierite, mullite, zirconium phosphate, aluminum titanate, silicon carbide, silicon-silicon carbide composite (e.g., Si-bonded SiC), cordierite-silicon carbide composite, zirconia, spinel, indialite, sapphirin, corundum, titania, silicon nitride, etc. Preferably, the sealing portion is formed of a material containing a total of 50% by mass or more of these ceramics, and more preferably of a material containing 80% by mass or more. It is even more preferable that the sealing portion has the same material composition as the molded body, as this allows the expansion rate during firing to be the same and leads to improved durability.

[0064] There are no particular restrictions on the method for producing the honeycomb molded body; in addition to the extrusion molding described above, injection molding, press molding, etc., can be used. Any method can be used to dry the obtained molded body, such as hot air drying, microwave drying, dielectric drying, reduced pressure drying, vacuum drying, or freeze drying. After drying the molded body, it is held in a firing furnace heated to 1300 to 1600°C, preferably 1350 to 1430°C, under atmospheric pressure for 3 to 105 hours to obtain the honeycomb base material 10.

[0065] In step S2, the outer surface of the honeycomb substrate 10 is ground to a predetermined size and shape. Grinding can be performed using a known method. If the desired size and shape are obtained after molding in step S1 and grinding is not necessary, the outermost surface of the honeycomb substrate 10 may not be ground, and step S2 may be omitted. When joining multiple honeycomb substrates 10 together, a bonding material may be applied to the outer surface wall of the honeycomb substrate 10 and heat-treated at approximately 200°C or lower to join the multiple honeycomb substrates 10 together via a bonding layer. As the bonding material, for example, one prepared by mixing anisotropic inorganic powder, aggregate, amorphous particles containing Si, and a dispersion medium such as water can be used.

[0066] As the material for the anisotropic inorganic powder, natural minerals or artificial ceramic fibers may be used. Suitable natural minerals include needle-shaped or plate-shaped natural minerals such as volastonite, mica, talc, sepiolite, palygoskite, and attapulgite. Suitable artificial ceramic fibers include RCF (amorphous refractory ceramic fiber mainly composed of alumina and silica), alumina fibers, mullite fibers, carbon fibers, silicon carbide fibers, boron nitride fibers, potassium titanate fibers, and zinc oxide fibers. The anisotropic inorganic powder may be used alone or in combination of two or more types.

[0067] Examples of aggregate materials include ceramics such as cordierite, mullite, zirconium phosphate, aluminum titanate, silicon carbide, silicon-silicon carbide composites (e.g., Si-bonded SiC), cordierite-silicon carbide composites, zirconia, spinel, indialite, sapphirin, corundum, titania, and silicon nitride.

[0068] Either an inorganic binder or an organic binder may be used. Examples of organic binders include methylcellulose, hydroxypropylmethylcellulose, carboxymethylcellulose, polyvinyl alcohol, and methylcellulose. Examples of inorganic binders include clay minerals such as bentonite, montmorillonite, sepiolite, and attapulgite. One type of binder may be used, or two or more types may be used in combination.

[0069] A dispersant such as polyethylene glycol oleate may be added to the bonding slurry. Examples of pore-forming materials include hollow or solid organic balloons such as foamed resins, water-absorbing resins, organic materials such as starch, and inorganic materials such as fly ash balloons. One type of pore-forming material may be used, or two or more types may be used in combination.

[0070] In step S3, the outer coating material is applied so as to surround the outer surface of the honeycomb substrate 10, and then dried and heat-treated to form an outer coating layer 13 on the outer surface of the honeycomb substrate 10, thereby creating the honeycomb structure 1.

[0071] Examples of outer perimeter coating materials include those prepared by mixing inorganic raw materials such as inorganic fibers, colloidal silica, clay, and ceramic particles with additives such as organic binders, pore-forming agents, and dispersants, along with water, to form a slurry. Furthermore, the method of applying the outer perimeter coating material is not particularly limited, and known methods can be used. It is preferable to use the grinding powder produced during the grinding process of the outer perimeter surface of the honeycomb substrate 10 in step S2 as the outer perimeter coating material, as this allows for effective utilization of the raw materials used to produce the honeycomb structure 1.

[0072] As the ceramic raw material powder for the outer periphery coating layer 13, for example, in order to form an outer periphery coating layer 13 on the outer surface of the honeycomb substrate 10 having pores with an average pore diameter A [μm] that is larger than the average pore diameter B [μm] of the honeycomb substrate 10, and with an average porosity P1 [%], cordierite particles with an average particle diameter D50 of 1 to 1000 μm can be used, more preferably 2 to 800 μm, and even more preferably 3 to 600 μm. When using SiC powder and metallic Si powder as the ceramic raw material powder, for example, the average particle diameter D50 of the SiC powder is preferably 5 to 50 μm, more preferably 7 to 40 μm, and even more preferably 9 to 30 μm. The average particle diameter D50 of the Si powder is preferably 2 to 12 μm, more preferably 3 to 10 μm, and even more preferably 4 to 8 μm. The average particle diameter D50 refers to the particle diameter corresponding to the 50% cumulative frequency in the volume-based cumulative particle size distribution measured by laser diffraction and scattering.

[0073] The outer coating material is prepared by adding clay material (additives) to this ceramic raw material powder. At least a binder and a pore-forming agent are used as additives. In addition to the binder and pore-forming agent, dispersants and surfactants can be used. The binder and pore-forming agent can be the same as those used for the honeycomb substrate 10. The particle size or fiber diameter (average diameter) of the pore-forming agent is preferably 5 to 300 μm, and more preferably 10 to 200 μm. Furthermore, it is preferable to use a pore-forming agent such that the average pore diameter A of the outer coating layer 13 is larger than the average pore diameter B of the honeycomb substrate 10, or a pore-forming agent with a larger particle size than the pore-forming agent used for the honeycomb substrate 10. In order to make the average pore diameter A of the outer coating layer 13 larger than the average pore diameter B of the honeycomb substrate 10, the particle size of the main raw material that serves as aggregate may be increased in addition to increasing the particle size of the pore-forming agent.

[0074] As a method for forming the outer perimeter coating layer 13, for example, a method can be used in which the honeycomb substrate 10 is placed on a rotating table and rotated, and the outer perimeter coating material is discharged from a blade-shaped coating nozzle while the coating nozzle is pressed against the outer perimeter of the honeycomb substrate 10. By using such a method, the outer perimeter coating layer 13 can be applied with a uniform thickness. In addition, the surface roughness of the formed outer perimeter coating layer 13 is reduced, resulting in an outer perimeter coating layer 13 that has an excellent appearance and is resistant to damage from thermal shock. The method for drying the outer perimeter coating material is not particularly limited. For example, from the viewpoint of preventing drying cracks, a method can be used in which 25% or more of the moisture in the outer perimeter coating material is dried by holding it at room temperature for 24 hours or more, and then moisture and organic matter are removed by holding it in an electric furnace at 600°C for 1 hour or more. If the cells 11 are to be sealed after the honeycomb structure 1 is formed, the cells may be sealed after the outer perimeter coating layer 13 is formed by pressing a paste-like material with a spatula such as a squeegee.

[0075] In step S4, a catalyst solution containing the catalyst to be supported on the honeycomb structure 1 is prepared, the honeycomb structure 1 is immersed in the catalyst solution, and the catalyst is supported using capillary action.

[0076] As a method for supporting the catalyst, a known dip-coating method in which the honeycomb structure 1 is immersed in the catalyst solution may be used, but this results in a large amount of catalyst being supported on the outer coating layer 13. In one embodiment, with one end face of the honeycomb structure 1 (e.g., the inlet end face 14) immersed, the honeycomb structure 1 is held perpendicular to the catalyst solution surface and held for a predetermined time. This holding allows the catalyst solution to be drawn up into the pores of the partition walls 12 of the honeycomb substrate 10 by capillary force, filling the pores with catalyst. Subsequently, the honeycomb structure 1 is inverted, and with the other end face (e.g., the outlet end face 15) immersed, the honeycomb structure 1 is held perpendicular to the catalyst solution surface and held for a predetermined time. This holding allows the catalyst solution to be drawn up into the pores of the partition walls 12 of the honeycomb substrate 10 by capillary force, filling the pores with catalyst. The suction of the catalyst solution from the end face using capillary force can be repeated multiple times. In another embodiment, the honeycomb structure 1 may be formed by a method such as suction, in which one end face of the honeycomb structure 1 (for example, the inlet end face 14) is immersed in the catalyst solution and the catalyst solution is drawn in from the other end face.

[0077] According to the manufacturing method of the honeycomb structure 1 according to an embodiment of the present invention, the honeycomb substrate 10 is provided with pores in the partition walls 12 having a pore diameter that causes capillary action, and the honeycomb structure 1 is formed in which the average pore diameter B of the honeycomb substrate 10 is smaller than the average pore diameter A of the outer periphery coating layer 13. When the catalyst is supported, more of the catalyst liquid penetrates into the pores of the partition walls 12 of the honeycomb substrate 10 than into the outer periphery coating layer 13 due to capillary action, making it possible to selectively attach the catalyst to the honeycomb substrate 10 while suppressing the adhesion of the catalyst to the outer periphery coating layer 13. [Examples]

[0078] Examples and comparative examples of the present invention are described below, but the technical scope of the present invention is not intended to be limited by these examples.

[0079] (Examples 1-12) As ceramic raw material powder, silicon carbide (SiC) powder and silicon (Si) powder were mixed in a mass ratio of 80:20, and appropriate amounts of a pore-forming agent (starch), an organic binder (hydroxypropyl methylcellulose), a surfactant (oleic acid ester), and water were added to obtain a clay base. A rectangular honeycomb molded body was produced by extrusion molding using this clay base. The columnar honeycomb molded body was degreased in an air atmosphere at approximately 450°C, and then fired in an Ar atmosphere at approximately 1450°C to obtain a rectangular honeycomb substrate with the following specifications.

[0080] Base shape: 35mm square Total length: 150mm Average porosity: As shown in Table 1 Average pore size: As shown in Table 1 Average thickness of the partition: 0.3 mm Cell cross-sectional shape: square Cell density: 46 cells / cm² 2 Average thickness of the outer perimeter sidewall: 0.5 mm

[0081] A bonding material was prepared by mixing anisotropic inorganic powder (mullite fiber), aggregate (silicon carbide, cordierite), pore-forming material (foamed resin), binder (carboxymethylcellulose), and dispersant (PEG monophosphate ester) in a mixer. This bonding slurry was applied to the side surface of the honeycomb substrate obtained in the above preparation procedure to a thickness of approximately 1 mm, and another honeycomb substrate obtained in the above preparation procedure was placed on top. This process was repeated to prepare a segmented laminate consisting of a total of 16 honeycomb substrates arranged in a 4x4 grid. The entire structure was then bonded together by applying external pressure as appropriate, and the segmented laminate was dried at 120°C for 2 hours to obtain the segmented laminate.

[0082] After grinding the outer periphery of the segmented joined body so that the outer shape thereof becomes a cylindrical shape, an outer peripheral coat layer of 1.5 mm in thickness was formed on the outer peripheral surface of the honeycomb base material on the processed surface. The outer peripheral coat layer was formed by adding a pore-forming agent so that the average pore diameter of the outer peripheral coat layer is larger than the average pore diameter of the honeycomb base material, and pressing a coating nozzle against the outer peripheral portion of the honeycomb base material to apply an outer peripheral coating material obtained at a ratio of grinding powder (SiC and metallic Si): 60, colloidal silica: 20, and alumina: 20 along the outer peripheral portion. This outer peripheral coating material was dried and fired at 600°C for 2 hours to fabricate honeycomb structures of Examples 1 to 12 having the average pore diameter and average porosity shown in Table 1. A catalyst was supported on each of the honeycomb structures of Examples 1 to 12. Table 1 shows the measurement results of the physical properties of the honeycomb base material and the outer peripheral coat layer of the honeycomb structures of Examples 1 to 12.

[0083] (Comparative Examples 1 to 2) As ceramic raw material powders, SiC powder and Si powder were mixed at a mass ratio of SiC powder : Si powder = 80:20, and the same pore former, organic binder, surfactant, and water as those in Examples 1 to 12 were added thereto to obtain a plastic kneaded clay. Using this kneaded clay, a rectangular honeycomb formed body was produced by extrusion molding. This honeycomb formed body was degreased at about 450°C in an air atmosphere and fired at about 1450°C in an Ar atmosphere to obtain a rectangular honeycomb base material having the following specifications

[0084] Bottom surface shape: square with a side length of 35 mm Total length: 150 mm Average porosity: as described in Table 1 Average pore diameter: as described in Table 1 Average thickness of partition walls: 0.3 mm Cell cross-sectional shape: square Cell density: 46 cells / cm 2 Average thickness of outer peripheral side wall: 0.5 mm

[0085] After grinding the outer circumference of the segment joint so that its outer shape was cylindrical, an outer coating layer 13 with a thickness of 1.5 mm and having the average pore diameter and average porosity described in Table 1 was fabricated on the machined surface of the honeycomb substrate 10. This outer coating material was dried and fired at 600°C for 2 hours to produce the honeycomb structures of Comparative Examples 1 and 2. The catalyst was supported on the honeycomb structures of Comparative Examples 1 and 2 in the same manner as in Examples 1 to 12. The measurement results of the physical properties of the honeycomb substrate and outer coating layer of the honeycomb structures of Comparative Examples 1 to 4 are shown in Table 1.

[0086] In Examples 1-12 and Comparative Examples 1-2, one end face of the honeycomb structure was immersed in the catalyst solution to support the catalyst by capillary action, and then the other end face was immersed in the catalyst solution to support the catalyst by capillary action. The catalyst coating performance was evaluated as follows: "○" if the target amount of catalyst could be supported on the honeycomb substrate and the amount of catalyst supported in the outer coating layer was less than the amount of catalyst supported in the honeycomb substrate; "△" if the amount of catalyst supported in the outer coating layer was less than the amount of catalyst supported in the honeycomb substrate, but catalyst seepage from the outer coating layer occurred; and "×" if the amount of catalyst supported in the outer coating layer was greater than the amount of catalyst supported in the honeycomb substrate, and the target amount of catalyst could not be coated on the honeycomb substrate.

[0087] [Table 1] [Explanation of Symbols]

[0088] 1: Honeycomb structure 10: Honeycomb substrate 11: Cell 12: Bulkhead 13: Outer coating layer 14:Inflow end face 15:Outflow end face

Claims

1. A columnar honeycomb substrate having porous partition walls that divide and form multiple cells that serve as fluid flow paths extending from the inlet end face to the outlet end face, A porous outer coating layer is disposed on the outer surface of the honeycomb substrate, Equipped with, A honeycomb structure in which the honeycomb substrate has pores in its partitions having a pore diameter that causes capillary action, and when the average pore diameter of the honeycomb substrate is B [μm] and the average pore diameter of the outer periphery coating layer is A [μm], the relationship B < A is satisfied.

2. When the average porosity of the honeycomb substrate is P2 [%] and the average porosity of the outer coating layer is P1 [%], then A > B × (P1 / P2) 0.2 A honeycomb structure according to claim 1 that satisfies the relationship.

3. When the average porosity of the outer coating layer is P1 [%], A < 670 - 1 / 6 × P1 2 A honeycomb structure according to claim 1 that satisfies the relationship.

4. The honeycomb structure according to any one of claims 1 to 3, wherein the average pore diameter B of the honeycomb substrate is 5 μm to 30 μm.

5. The honeycomb structure according to any one of claims 1 to 3, wherein the average pore diameter A of the outer peripheral coating layer is greater than 5 μm and less than or equal to 500 μm.

6. The honeycomb structure according to any one of claims 1 to 3, wherein the average porosity P2 of the honeycomb substrate is 20 to 70%.

7. The honeycomb structure according to any one of claims 1 to 3, wherein the average porosity P1 of the outer periphery coating layer is 30 to 75%.

8. The aforementioned honeycomb substrate comprises a plurality of honeycomb substrates, The plurality of honeycomb substrates are joined together by a bonding layer that joins the plurality of honeycomb substrates together. The honeycomb structure according to any one of claims 1 to 3, wherein the outer peripheral coating layer is arranged to surround the outer peripheral surfaces of the plurality of honeycomb substrates joined by the bonding layer.

9. A columnar honeycomb substrate having porous partition walls that divide and form multiple cells that serve as fluid flow paths extending from the inlet end face to the outlet end face, A porous outer coating layer is disposed on the outer surface of the honeycomb substrate, Equipped with, A honeycomb filter wherein the honeycomb substrate has pores in its partitions having a pore size that causes capillary action, a catalyst is supported on the partitions, and when the average pore size of the honeycomb substrate is B [μm] and the average pore size of the outer periphery coating layer is A [μm], the relationship B < A is satisfied.

Citation Information

Patent Citations

  • Device of grasping and holding loading machine

    JP1979031158A

  • Ceramic honeycomb structure, its forming process, and coating material for the same

    JP2004075523A

  • Honeycomb filter and its manufacturing method

    JP2009183835A